Step-by-step explanation:
1) Your problem → (4x^2 - 17x^3 + 9) - (x^2 + 9x + 23x^2 + 11)
(-17x^3+4x^2+9)-(x^2+23x^2+9x+11)
=-17x^3+4x^2+9-x^2-23x^2-9x-11
=-17x^3+4x^2-x^2-23x^2-9x+9-11
=-17x^3-20x^2-9x-2
2) Your problem → 0 - 19.73 - 25x^2 - 12x - 3
=0-19.73-25x2-12x-3
=-25x^2-12x-22.73
3) - 10.x^3 – 162x^2 – 24x - 4
4) Your problem → 17x^3 - 20x^2 - 9x^2
=17x^3-20x^2-9x^2
=17x^3-29x^2
5) -16x^3 – 243x^2 – 12x – 3
F(x)=-9/x which is equal to:
f(x)=-9x^(-1) So the power rule for differentiation is used...
Power rule: f(x)=x^e, df/dx=ex^(e-1) so:
df/dx=-9(-1)x^(-1-1)
df/dx=9x^(-2) or if you prefer...
df/dx=9/x^2
df/dx(6)=9/36=1/4
Answer:
3n + 2
Step-by-step explanation:
Answer:
1/2
Step-by-step explanation:
Amswer
it is b Step-by-step explanation: